A companion to religion in late antiquity - Lössl, Josef; Baker-Brian, Nicholas, 1973- (Blackwell companions to the ancient world., 2018)
A Companion to Religion in Late Antiquity offers an authoritative and comprehensive survey of religion in Late Antiquity. This historical era spanned from the second century to the eighth century of the Common Era. With contributions from leading scholars in the field, the Companion explores the evolution and development of religion and the role various religions played in the cultural, political, and social transformations of the late antique period.